2007
DOI: 10.1186/1743-422x-4-106
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous presence and expression of human hepatitis C virus (HCV), human herpesvirus-6 (HHV-6), and human immunodeficiency virus-1 (HIV-1) in a single human T-cell

Abstract: We have developed a system that isolates and replicates HCV in vitro. These isolates are called CIMM-HCV. This system has made it possible to analyze the biology, nature, and extent of HCV variability, among other things. Individuals that are infected with HIV-1 are often also infected with HCV and HHV-6. In addition to HCV, our lab has systems for replicating HIV-1 and HHV-6. We asked whether all these viruses could infect the same cells. We report here the successful infection of a T-cell (CEM) by CIMM-HCV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Comparison of sequences of the 5'UTR for HCV samples containing deletions or that were genotype 3 provided evidence that cord blood macrophages select for 5'UTR sequences similar to HCV genotype 1 [ 144 , 145 ]. As both macrophages and T cells can be infected by HCV using this system, the system has been used to co-infect T cells with HCV, HIV, and HHV-6 [ 146 ]. Cells containing all three viruses were observed (Figures 4 and 5 ), demonstrating that this isolation system can be used to study co-infection by these three viruses.…”
Section: Which Cell Types Are Permissive For Hcv Replication mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of sequences of the 5'UTR for HCV samples containing deletions or that were genotype 3 provided evidence that cord blood macrophages select for 5'UTR sequences similar to HCV genotype 1 [ 144 , 145 ]. As both macrophages and T cells can be infected by HCV using this system, the system has been used to co-infect T cells with HCV, HIV, and HHV-6 [ 146 ]. Cells containing all three viruses were observed (Figures 4 and 5 ), demonstrating that this isolation system can be used to study co-infection by these three viruses.…”
Section: Which Cell Types Are Permissive For Hcv Replication mentioning
confidence: 99%
“… Electron micrograph of mature (black arrow) and immature (red arrow) HCV from in vitro infected T-cell . Picture adapted from reference [ 146 ]. …”
Section: Which Cell Types Are Permissive For Hcv Replication mentioning
confidence: 99%
“…Human herpesvirus 6 species A and B (HHV-6A and HHV-6B; Ablashi et al 1991 ; Dagna et al 2013 ; Salahuddin et al 2007 ) and HHV-7 (Frenkel et al 1990 ) have been regarded as lymphotropic and neurotropic viruses (Ablashi et al 2000 ; Chapenko et al 2016 ; Savolainen et al 2005 ). In Africa, 86–100% of infants acquire HHV-6A without specific symptoms (Bates et al 2009 ; Hall et al 2006 ; Kasolo et al 1997 ; Sjahril et al 2009 ), but a recent study has shown that in biobanked sera specimens from hospitalized Zambian children between 3 weeks and 2 years of age who were admitted with febrile illness, HHV-6B DNAemia was predominant over HHV-6A (20.5 % versus 0.3 %; Tembo et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Individual cells were able to support replication of all three viruses without dominance of one virus. All these viruses are highly cytolytic, and therefore triplyinfected cells were short lived (Salahuddin et al, 2007). There are several reports concerning the inhib i t o r y e f f e c t o f H H V -6 o n H I V -1 i n c e l l cultures.…”
Section: In Vitro Studies On the Intracellular Transactivation Of Hivmentioning
confidence: 99%